Comparing and determining factors associated with hypertension self-care profiles of patients in two multi-ethnic Asian countries: cross-sectional studies between two study populations - Yi, Sabrina Mei Wee; Salim, Hani; Mawardi, Maliza; Koh, Yi Ling Eileen; Ali, Hanifatiyah; Ghazali, Sazlina Shariff; Lee, Ping Yein; Ching, Siew Mooi; Shamsuddin, Nurainul Hana; Tan, Ngiap Chuan (BMJ Publishing Group, 2021)
Objectives To compare the sociodemography, disease characteristics and hypertension self-care profiles and to determine the factors influencing Hypertension Self-Care Profiles (HTN-SCP) in two populations in primary care settings from Singapore and Malaysia. Design Cross-sectional, cross national. Setting Multi-centre, primary care clinics Malaysia and Singapore. Participants 1123 adults with hypertension enrolled and analysed. Primary and secondary outcome measures Comparison between sociodemography, disease characteristics and the mean scores of HTN-SCP domains (behaviour, motivation and self-efficacy) and the factors influencing hypertension self-care. Results 1123 adults with hypertension attending primary care clinics in Malaysia and Singapore were involved. The participants’ mean age was 63.6 years (SD 9.7) in Singapore and 60.4 (SD 9.1) in Malaysia. Most of the participants in Singapore had tertiary education (22.3%) compared with Malaysia (13.0%), p<0.001. A higher proportion of participants from Singapore had controlled blood pressure (74.6%) compared with Malaysia (33.8%), p<0.001. The mean total score of HTN-SCP was significantly higher among Singapore participants compared with Malaysia participants 190 (SD 28) versus 184 (SD 23) (p<0.001). Similarly, the mean score for motivation domain 67 (SD 10) versus 65 (SD 9), followed by self-efficacy score 65 (SD 11) versus 62 (SD 9) and behaviour score (58 SD 9 vs 56 SD 9) were higher among Singapore participants. In both countries, the factors which influenced higher HTN-SCP mean scores across all domains were being Indian and had tertiary education. Conclusions The study population in Singapore had a higher HTN-SCP mean score compared with Malaysia. The common factors influencing higher HTN-SCP mean scores at both study sites were ethnicity and level of education. Future intervention to improve self-care among people with hypertension may need to be tailored to their behaviour, motivation and self-efficacy levels.